2023
DOI: 10.1093/jac/dkad174
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the third-generation tetracycline resistance of multidrug-resistant livestock-associated methicillin-resistant Staphylococcus aureus ST9 across healthcare settings in China

Abstract: Background The overuse of antibiotics in livestock is contributing to the burden of antimicrobial resistance in humans, representing a One Health challenge. Livestock-associated methicillin-resistant Staphylococcus aureus (LA-MRSA) has recently become a growing concern, and ST9 is the major LA-MRSA lineage in China and has emerged in clinical settings. Methods Antimicrobial susceptibility testing was used to evaluate the tetr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…In recent years, the carriage of multiple ccr gene complexes has been presented by a Chinese LA-MRSA ST9 from clinical and porcine isolates [26]. In addition, another study from China has reported the presence of coagulase-negative staphylococci (CoNS) carrying multiple SCCmec elements [27].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, the carriage of multiple ccr gene complexes has been presented by a Chinese LA-MRSA ST9 from clinical and porcine isolates [26]. In addition, another study from China has reported the presence of coagulase-negative staphylococci (CoNS) carrying multiple SCCmec elements [27].…”
Section: Discussionmentioning
confidence: 99%
“…Tetracyclines are a class of broad-spectrum antibiotics, including naturally occurring and semi-synthetic tetracyclines ( Roberts, 2003 ). Due to their side-effects, the use of tetracyclines is limited in human clinics, but they are still been used globally as important infection treatment measures and growth promoters among livestock animals which promoted the tetracycline resistant determinants transmission in livestock products ( Inglis et al, 2019 ; Chen et al, 2023 ). Since animals cannot fully absorb or metabolize tetracyclines, they excrete a significant fraction of such drugs or of their breakdown products into the environment via feces or urine which may also promote the transmission of resistant determinants ( Mackie et al, 2006 ).…”
Section: Discussionmentioning
confidence: 99%